Impact of inflammation-induced oxidative stress on the integrity of immuno-haematopoietic cells and potential ameliorating interventions in an in vitro HIV model - Wanjiku, Samuel Mburu (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.